Erosion Hazard Vulnerability and Soil Fertility Status in Forest Plantation Concession in Central Kalimantan - Iskandar, Wahyu; Hendrayanto; Muhammad Nizar, Zulkarnaen; Jung, Yoonhwa (Jurnal Ilmu Tanah dan Lingkungan, 2023)
Land cover changes alter surface run off rate and erosion rate as well. The land clearing, as a part of the implementation of silvicultural system of forest plantation (THPB) remove all of vegetative covers which temporarily reduce evapotranpiration and hence increase surface erosion. Surface erosion may erode soil particles, leach nutrients and decrease soil fertility. This research estimated and mapped the rate of erosion, erosion hazard vulnerability, and soil fertility status in forest plantation concession in Central Kalimantan. The results showed that soil rate under Acacia, Eucalyptus, DPSL (undisturbed area), Harvesting Area and Skidding Road are: 3.0, 3.2, 1.5, 4.8, dan 5.0 (ton ha-1 year-1), respectively. Although erosion rate was relatively high, such as in the Harvesting and Skidding Road, the erosion hazard vulnerability (TBE) was still low due to deep soil stratum. Based on the analysis of soil samples, almost all areas had low pH and fertility.